Integrating Maqasid Sharia in Responsible Tourism Marketing: A Case Study of Rinding Allo Village Attractions - Iradat, Muhammad Isra; Asmayanti; Syarifah Aliyah Fitrisam (LAA MAISYIR : Jurnal Ekonomi Islam, 2025)
Tourism necessitates the adoption of sustainability principles to preserve the authenticity of tourism products. Rinding Allo Village, as an emerging tourist destination, has shown potential but pays limited attention to carrying capacity, thereby risking negative impacts from tourism activities. This research aims to integrate maqasid sharia into the framework of Responsible Tourism Marketing (RTM) through a case study of tourism attractions in Rinding Allo Village. Employing a qualitative approach with a case study design, data were collected through interviews, direct observation, and documentation. The data were then analyzed using a within-case analysis method, focusing on marketing planning through the segmentation, targeting, and positioning (STP) framework. The findings reveal that the tourism attractions in Rinding Allo Village have significant potential to support the integration of maqasid sharia into RTM. Specific attractions include: Rentekasimpo Waterfall, which reflects environmental preservation (hifz al-bi’ah); Buntulemo agro-tourism, which supports the maintenance of natural ecosystems (hifz al-nafs); Pangngaru dance performances, symbolizing respect and social dignity (hifz al-‘ird); and the traditional weaving of Rongkong cloth, representing the preservation of local wisdom (hifz al-‘ird). As a strategic recommendation, the development of a tourism guidebook is proposed as part of enhancing the destination’s carrying capacity and promoting responsible tourism practices aligned with Islamic ethical values.